Strategi Komunikasi Advokat Dalam Membangun Kepercayaan Klien: Ditinjau Dari Pendekatan Hukum - Khairun, Imarroh Lutfiyatul Laeli; Ardelia, Talita Adwa; Aprilia, Salsabila Nisa; Imon, Syarah Adilla (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Client trust is the primary foundation in the professional relationship between lawyers and their clients. The success of a lawyer in defending the legal interests of a client is not only determined by legal competence but also by effective and strategic communication skills. This study aims to analyze the communication strategies employed by lawyers in building and maintaining client trust, using a qualitative approach through case studies and in-depth interviews. The findings indicate that transparency, empathy, consistency of information, and the use of easily understandable language are key elements in lawyer-client communication. Furthermore, a client-oriented legal approach, professional ethics, and the fulfillment of client rights form the basis of every communication strategy applied. These findings contribute to strengthening the professional ethics of lawyers and improving the quality of legal services in Indonesia.